1999
DOI: 10.1042/bj3440061
|View full text |Cite
|
Sign up to set email alerts
|

Aggrecanase versus matrix metalloproteinases in the catabolism of the interglobular domain of aggrecan in vitro

Abstract: The importance of aggrecanase versus matrix metalloproteinase (MMP) enzymic activities in the degradation of aggrecan in normal and osteoarthritic (OA) articular cartilage in vitro was studied in order to further our understanding of the potential role of these two enzyme activities in aggrecan catabolism during the pathogenesis of cartilage degeneration. Porcine and bovine articular cartilage was maintained in explant culture for up to 20 days in the presence or absence of the catabolic stimuli retinoic acid,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
1

Year Published

2000
2000
2003
2003

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 115 publications
(30 citation statements)
references
References 38 publications
1
28
1
Order By: Relevance
“…Although it has been widely accepted (22,23,30,(37)(38)(39)(40)(41)(42) that ADAMTS4 (aggrecanase-1) cleaves only at the Glu 373 -Ala 374 bond within the IGD, the results described here suggest that both of the major cleavages that are known to occur in vivo, at Glu 373 -Ala 374 and Asn 341 -Phe 342 , can be catalyzed by ADAMTS4. Previously, cleavage at the Asn 341 -Phe 342 site in the aggrecan IGD was considered a specific property of the MMP family, with the exception of a snake venom enzyme (30,34) 341 -Phe 342 bond in the experiments described here was due to contamination of the ADAMTS4 preparation with an MMP-like activity was eliminated by the observation that although 10 mM EDTA and TIMP-3 totally blocked the cleavage, neither TIMP-1 nor TIMP-2 was inhibitory, even at 750 nM.…”
Section: Discussionmentioning
confidence: 68%
“…Although it has been widely accepted (22,23,30,(37)(38)(39)(40)(41)(42) that ADAMTS4 (aggrecanase-1) cleaves only at the Glu 373 -Ala 374 bond within the IGD, the results described here suggest that both of the major cleavages that are known to occur in vivo, at Glu 373 -Ala 374 and Asn 341 -Phe 342 , can be catalyzed by ADAMTS4. Previously, cleavage at the Asn 341 -Phe 342 site in the aggrecan IGD was considered a specific property of the MMP family, with the exception of a snake venom enzyme (30,34) 341 -Phe 342 bond in the experiments described here was due to contamination of the ADAMTS4 preparation with an MMP-like activity was eliminated by the observation that although 10 mM EDTA and TIMP-3 totally blocked the cleavage, neither TIMP-1 nor TIMP-2 was inhibitory, even at 750 nM.…”
Section: Discussionmentioning
confidence: 68%
“…Aggrecanase-derived 374 ARGSV fragments are the major aggrecan products found in synovial fluids from arthritis patients (7,8). Furthermore, the aggrecanase-derived ITEGE 373 neoepitope at the C terminus of the G1 domain has been detected in human (9,10), bovine (11,12), pig (12), and rat (11) cartilage and in mice with experimental arthritis (13,14).…”
mentioning
confidence: 99%
“…The 342 FFGVG N-terminal neoepitope (Fig. 1c) has been found in human synovial fluids (16) and conditioned medium from porcine (22) and human osteoarthritic (12) cartilage cultures. The C-terminal neoepitope DIPEN 341 ( Fig.…”
mentioning
confidence: 99%
“…Cleavage of aggrecan is enhanced in inflammatory joint disease resulting in cartilage damage, indeed soluble products of aggrecan catabolism generated by aggrecanases and MMPs can be found in synovial fluid and cartilage extracts of patients with arthritis (14, 20 -22). In vitro culture systems have also demonstrated that a variety of inflammatory cytokines, such as IL-1␣ and TNF-␣ stimulate cleavage at these same sites (23)(24)(25)(26). The enzyme cleavage sites, and the minimal sequence lengths for recognition by target enzymes, have been previously documented (27)(28)(29)(30).…”
Section: Complement (C)mentioning
confidence: 99%
“…All of these reagents are known stimulators of cartilage catabolism. IL-1␣ and TNF-␣ are known to up-regulate the production of the aggrecanases and some MMPs, whereas retinoic acid is known to up-regulate the production of the aggrecanases but not the MMPs (23)(24)(25)(26)40). Following incubation of chondrocytes with these reagents and the DAF4-IGD75-IgG 4 prodrug, the neoepitopes generated by the aggrecanases and MMPs were detected using BC-3 and This generated a reagent with little Cregulatory activity until cleaved by MMPs at the site of inflammation, resulting in release of the active DAF moiety (C).…”
Section: Cleavage Of Prodrugs By Enzymementioning
confidence: 99%